Host response to fungal infections – how immunology and host genetics could help to identify and treat patients at risk (Swiss Medical Weekly, 2016)
In spite of the ever-increasing incidence and poor outcome of invasive fungal infections in immune compromised patients, there is currently no reliable method to accurately predict the risk, to monitor the outcome and to treat these infections. Protective immunity against Candida and Aspergillus depends on a highly coordinated interaction between the innate and adaptive immune systems. Genetic and immunological defects in components of these networks result in increased risk of invasive fungal infections among patients undergoing chemotherapy or transplant recipients. We review the most important genetic and immunological factors that influence human susceptibility to Candida and Aspergillus infections and discuss the potential role of basic research to promote precision medicine for infectious diseases. We discuss how immunogenetic studies can help to provide tools for improved identification of high-risk patients and the development of tailored antifungal therapies.